HUBUNGAN PARENTAL MONITORING DAN PENGARUH TEMAN SEBAYA DENGAN PERILAKU SEKSUAL BERESIKO PADA REMAJA - Widya Nengsih, Ainal Mardiah, Weni Novriani (Maternal Child Health Care, 2021)
When entering adolescence, sexual stimulation in adolescents begins to increase. High about sexual stimulation causes adolescents, to carry out risky sexually behavior, so that it will have a bad impact on adolescent, even sexually transmitted diseases such as HIV / AIDS and Pregnancy out of wedlock. Risky sexual behavior cannot be separated from peer involvement and parental supervision. The purpose of this study was to determine The Correlation between Parental Monitoring and the Influence of Risky Peers Sexual behavior in Teenagers at SMA A, Pesisir Selatan Regency in 2021.This studywas conducted on March – July 2021 at SMA A, Pesisir Selatan Regency. This type of this study was a analitical correlational study with 60 students in the second grade were chosen as the samples. They had been chosen by total sampling technique. The data were collected through a questionnaire. Then, it was analyzed by chi square test. The results showed that there was a relationship between parental monitoring and risky sexual behavior (p=0.004) and the influence of risky peer sexual behavior (p=0.004). Parents are expected to be able to carry out supervision by increasing control over adolescent in daily life, to the school so thT they can reactivate counseling guidance. health servics are expected to be able to carry out socialization and health education about sexual problems so that adolescents avoid risky sxual behavior.